2018
DOI: 10.48048/wjst.2019.5572
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sound and Vibration on Postural Balance in Healthy Young Adults

Abstract: Postural balance is influenced by alteration of somatosensory inputs. Sound and vibratory senses, one of several human senses may assist the postural control in a specific impaired situation. The aim of this pilot study was to quantify the effect of sound and vibration on postural balance in healthy young adults. Ten healthy young subjects volunteered to participate in the study. The average age, weight, height, and body mass index were 21.88 ± 0.42 years, 56.21 ± 9.80 kg, 159.75 ± 5.20 cm, and 21.99 ± 3.52 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Also, Yilmaz et al [29] proposed some synergistic effects of the combined exposure to noise and vibration on the vestibular system disturbances. In contrast, Bovonsunthonchai et al [30] demonstrated that there were not any interaction effects of sound and vibration on body equilibrium. The authors mentioned that their method, sample size, and participants' ages could affect the results of their study.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Also, Yilmaz et al [29] proposed some synergistic effects of the combined exposure to noise and vibration on the vestibular system disturbances. In contrast, Bovonsunthonchai et al [30] demonstrated that there were not any interaction effects of sound and vibration on body equilibrium. The authors mentioned that their method, sample size, and participants' ages could affect the results of their study.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it seems that the considered noise dose (85 dB(A) for 40 min of exposure) was not adequate for observing noticeable body balance changes in exposure to noise alone in the current study. Besides, the possible compensatory role of the Central Nervous System (CNS) for deficits in vestibular system functions can become active during the experience of single exposure to noise [29,30]. Second, auditory stimuli are less influential in body balance in comparison with vestibular, visual, and somatosensory inputs [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation